Objective and subjective image quality with prospectively gated versus ECG-controlled tube current modulation using 256-slice computed tomographic angiography - Abazid, Rami (Journal of the Saudi Heart Association, 2015)
INTRODUCTION: Radiation exposure is one of the major limitations of computed tomographic coronary angiography (CTA). The purpose of this study was to compare the objective and subjective image quality and radiation dose using prospective ECG gating (PGA) versus ECG-controlled tube current modulation (ECTCM) scanning techniques